Highly polymorphic microsatellite loci for the Parsley frog (Pelodytes punctatus): characterization and testing for cross-species amplification - Van De Vliet, M. S. (2014)
A microsatellite library was developed using genomic DNA of the Parsley frog, Pelodytes punctatus, an amphibian species which inhabits Mediterranean temporary pond systems. Number of alleles and heterozygosity ranged from 10 to 25 and from 0.66 to 0.90, respectively. Crossspecies amplification was successful for 13 of the 15 developed loci for the related species, Pelodytes ibericus. The high levels of polymorphism revealed by these loci will be extremely useful for characterizing the population genetic diversity and structure and to estimate levels of dispersal and gene flow in the species P. punctatus and P. ibericus.